Endogenous foreign capital flow in a CGE model for Brazil: The role of international reserves - Wilfredo Leiva Maldonado; Octávio Augusto Fontes Tourinho; Marcos Valli (Institute for Applied Economic Research (ipea), 2015)
In this paper we model foreign capital flow to Brazil as stemming from an investment decision that whose risk depends on the expected rate of loss of foreign reserves. This motivates the estimation of an empirical relationship between these two variables that is valid for "normal" periods (when there is no foreign exchange crisis) which is used to calculate the capital flow associated with a given expected rate of foreign reserves loss. This empirical relationship is then introduced in a static General Equilibrium Model for Brazil which has exogenous foreign capital flow and follows a relatively standard specification, to produce a version of it with endogenous capital flow. After employing the inverse of the estimated relationship to calculate the difference between the expected and the realized values of the reserve loss in 1998, and using it to adjust the base year data, we recalibrate the model and compare the response of the two versions of the model to a simulation of the implementation of two free trade agreements: with the Americas (ALCA) and with the European Union. The main conclusion is that the inclusion of endogenous foreign capital flow in the model significantly amplifies, and in some cases changes, the real effects of these free trade agreements.
Keywords: C68; F11; F17; 330